Interleukin‐6 potentiates endurance training adaptation and improves functional capacity in old mice. Issue 2 (22nd February 2022) - Leuchtmann, Aurel B.; Furrer, Regula; Steurer, Stefan A.; Schneider‐Heieck, Konstantin; Karrer‐Cardel, Bettina; Sagot, Yves; Handschin, Christoph
Abstract: Background: Interventions to preserve functional capacities at advanced age are becoming increasingly important. So far, exercise provides the only means to counteract age‐related decrements in physical performance and muscle function. Unfortunately, the effectiveness of exercise interventions in elderly populations is hampered by reduced acceptance and compliance as well as disuse complications. We therefore studied whether application of interleukin‐6 (IL‐6), a pleiotropic myokine that is induced by skeletal muscle activity and exerts broad systemic effects in response to exercise, affects physical performance and muscle function alone or in combination with training in aged mice. Methods: Sedentary old male mice (Sed+Saline, n  = 15) were compared with animals that received recombinant IL‐6 (rIL‐6) in an exercise‐mimicking pulsatile manner (Sed+IL‐6, n  = 16), were trained with a moderate‐intensity, low‐volume endurance exercise regimen (Ex+Saline, n  = 13), or were exposed to a combination of these two interventions (Ex+IL‐6, n  = 16) for 12 weeks. Before and at the end of the intervention, mice underwent a battery of tests to quantify endurance performance, muscle contractility in situ, motor coordination, and gait and metabolic parameters. Results: Mice exposed to enhanced levels of IL‐6 during endurance exercise bouts showed superior improvements in endurance performance (33% more work and 12% greater peak power compared with baseline), fatigue resistance in situ ( P  = 0.0014 vs . Sed+Saline; P  = 0.0199 vs . Sed+IL‐6; and P  = 0.0342 vs . Ex+Saline), motor coordination (rotarod performance, P  = 0.0428), and gait (gait speed, P  = 0.0053) following training. Pulsatile rIL‐6 treatment in sedentary mice had only marginal effects on glucose tolerance and some gait parameters. No increase in adverse events or mortality related to rIL‐6 treatment was observed. Conclusions: Administration of rIL‐6 paired with treadmill running bouts potentiates the adaptive response to a moderate‐intensity low‐volume endurance exercise regimen in old mice, while being safe and well tolerated.